Susceptibility to hepatotoxicity in transgenic mice that express a dominant-negative human keratin 18 mutant. - Ku, N O (1996)
Keratins 8 and 18 (K8/18) are intermediate filament phosphoglycoproteins that are expressed preferentially in simple-type epithelia. We recently described transgenic mice that express point-mutant human K18 (Ku, N.-O., S. Michie, R.G. Oshima, and M.B. Omary. 1995. J. Cell Biol. 131:1303-1314) and develop chronic hepatitis and hepatocyte fragility in association with hepatocyte keratin filament disruption. Here we show that mutant K18 expressing transgenic mice are highly susceptible to hepatotoxicity after acute administration of acetaminophen (400 mg/Kg) or chronic ingestion of griseofulvin (1.25% wt/wt of diet). The predisposition to hepatotoxicity results directly from the keratin mutation since nontransgenic or transgenic mice that express normal human K18 are more resistant. Hepatotoxicity was manifested by a significant difference in lethality, liver histopathology, and biochemical serum testing. Keratin glycosylation decreased in all griseofulvin-fed mice, whereas keratin phosphorylation increased dramatically preferentially in mice expressing normal K18. The phosphorylation increase in normal K18 after griseofulvin feeding appears to involve sites that are different to those that increase after partial hepatectomy. Our results indicate that hepatocyte intermediate filament disruption renders mice highly susceptible to hepatotoxicity, and raises the possibility that K18 mutations may predispose to drug hepatotoxicity. The dramatic phosphorylation increase in nonmutant keratins could provide survival advantage to hepatocytes.